A Fundamental Study on an SAP Mixed Asphalt Mixture for Reducing the Urban Heat Island Effect - Dae-Seong Jang; Chi-Su Lim; Kanghwi Lee; Cheolmin Baek (Applied Sciences)
As the average temperature in summer rises and heat waves occur more frequently, the urban heat island (UHI) phenomenon is becoming a social problem. Asphalt road pavement stores heat during the day, raising the surface temperature, and releases the stored heat at night, thereby aggravating the UHI phenomenon. Government authorities often spray water to lower the temperature of road pavement for the safety and convenience of citizens. However, the effect is immediate and does not last long. Therefore, in order to reduce the urban heat island phenomenon by spraying water, the recovery time of the surface temperature must be delayed. In this study, Super Absorbent Polymer (SAP), a highly absorbent polymer that absorbs 100 to 500 times its weight in water, was applied to asphalt road pavement. SAP is commonly used in diapers, feminine hygiene products, soil moisturizers, and concrete, and its scope is gradually expanding. The purpose of this study is to reduce the urban heat island phenomenon by mixing the SAP into asphalt and to increase the latent heat flux by evaporating the water absorbed by the SAP, thereby delaying the recovery time of the surface temperature of the road pavement. In this study, the performance of asphalt mixtures mixed with the SAP and the thermal characteristics according to the mixing amount were analyzed. In this study, the physical properties and temperature reduction performance of the asphalt mixture according to the SAP type and content were studied. The results of indoor and outdoor experiments on asphalt mixtures using the SAP showed that they satisfied the mechanical performance criteria as asphalt pavement materials and that the temperature recovery delay effect was improved.